Effect of renal sympathetic nerve stimulation on proximal water and sodium reabsorption. - Bell-Reuss, E (1976)
The renal responses to sympathetic nerve stimulation were studied in saline-expanded rats. The left kidney was partially denervated by crushing the left greater splanchnic nerve. Then the distal portion of the nerve was stimulated with square wave pulses of 0.5 ms duration, voltage twice threshold, and 1 or 2 Hz frequency while monitoring the compound action potential. Fibers with conduction speeds of 13-17 m-s-1 and of 0.7-1 m-s-1 were identified. Only stimulation of the latter appeared to produce changes in renal Na and water excretion. Whole kidney and individual nephron studies were performed alternating control and nerve stimulation periods. Nerve stimulation produced approximately a 25% reduction of the left kidney urine volume and sodium excretion. Glomerular filtration rate and renal plasma flow remained unchanged. Right kidney Na and water excretion, glomerular filtration rate, and renal plasma flow remained constant. In the left kidney, during nerve stimulation, the tubular fluid to plasma inulin concentration ratio increased significantly in the late proximal tubule. We conclude that the antidiuresis and antinatriuresis seen during sympathetic nerve stimulation were caused by increased sodium and water reabsorption in the proximal tubule, probably mediated by the stimulation of slowly conducting unmyelinated fibers. These responses appeared to be unrelated to systemic or intrarenal hemodynamic changes.